Currency Crises : In Search of Common Elements - Salgado, Ranil; Aziz, Jahangir; Caramazza, Francesco (Washington, D.C. : International Monetary Fund, 2000)
The paper seeks to identify common characteristics among a variety of macroeconomic and financial variables for a large sample of currency crises in industrial countries and emerging market economies. It covers crises which culminated in large currency depreciation as well as those in which there was a substantial loss of foreign reserves. The analysis involves comparing the monthly or annual pattern of movement of the various macroeconomic and financial variables around the time of crisis to their behavior during tranquil periods. The robustness of the results is tested by subdividing the sample into different types of currency crises and carrying out a similar analysis for each.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet